Helium isotopes in Plinian and inter-Plinian volcanic products of Vesuvius, Italy - Gherardi, Fabrizio; Barsanti, Mattia; Principe, Claudia; Magro, Gabriella (Frontiers in Earth Science, 2022)
We investigated helium isotopes on gas extracted by crushing from melt and fluid inclusions in minerals from Plinian and inter-Plinian tephra and lavas of Vesuvius, Italy. Erupted products of different ages were considered, from Avellino eruption (1995 BCE) to the last eruption of 1944, with special focus on the 79AD Plinian eruption. 3He/4He ratios between 1.5 to 2.7Ra were measured, with the highest values associated with rocks representative of the roof and the walls of the magma chambers (cumulates). Lowest values occurred in sanidines representative of magma-skarn interfaces. Noteworthy, the highest measured values of the 79AD pumices were comparable with both lavas and tephra emitted from flank vents and under open-conduit conditions during the Medieval Period and Present Period of Vesuvius activity, and present-day fumarolic discharges. 3He/4He values are buffered within an extended, deep-seated reservoir at about 10km filled with magma rising from the mantle. A fact that might potentially limit the accuracy of future eruption forecasting through monitoring of changes in 3He/4He ratio in Vesuvius fumaroles. Ageing and interaction with crustal rocks emerged as possible mechanisms that lowered the 3He/4He ratio of the melt during its intra-crustal magma chambers stay, with highest 3He/4He values associated with more dynamic conditions.